Treatment of Wedge-Shaped Dental Defects with the Combined Use of Hydroxyapatite and Fluoride-Containing Drugs and Measures for their Prevention in Undergrowth - Kuryazov Sh. A; Ashurova N. G. (International Journal on Integrated Education, 2021)
The relevance of the topic. The structure of wedge-shaped dental defects is getting younger every year. Today, a wedge-shaped tooth defect occurs at the age of 20 years, and sometimes in adolescents. Previously, it was believed that this is a pathology of people over forty years old [2.4.6.8].